Agriculture in FY21 budget: Paying farmers keeps them poor - Kishore, Avinash (Indian Express Group, 2020)
The finance minister, in her FY21 budget speech, announced a 16-point agenda to kickstart growth in agriculture and farmers’ income. While the agenda makes sense, following the money presents a disconcerting prospect. Less than 10% of the Rs 2.2 lakh crore budgeted for agriculture will support capital formation or R&D. Economies can’t grow without investment and innovation. This budget provides money for neither.